2009
DOI: 10.1007/s11055-009-9140-8
|View full text |Cite
|
Sign up to set email alerts
|

Slow-Wave Oscillations in the Craniosacral Space: A Hemoliquorodynamic Concept of Origination

Abstract: The mechanism of formation of rhythmic, slow-wave oscillations in the craniospinal cavity were studied. Synchronous bioimpedance traces were made of the head and lumbosacral part of the spine in five healthy young subjects at rest and during voluntary breath-holding; these reflect changes in the ratios of blood and CSF volumes in these parts of the craniospinal space. Computer amplitude-frequency and spectral analysis of the data (Macintosh G-4, Chart-5.2) demonstrated slow (6-12 cycles/min) and rapid (pulsati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…As studies on palpated and measured rates of head movements have shown a wide range (review in Nielson et al 2006), it is possible that different studies may report on different rhythms under the same name, the CRI. Previous reported experimental studies had found a CRI range from 6 -14 cpm ( Moskalenko et al 2001, 2004, 2009, Upledger and Karni 1979, Lockwood and Degenhardts 1998 comparable with the first palpation study (Woods and Woods 1961) reporting a CRI range of 10 -14 cpm. As the mentioned studies above did not report separation of the CRI and the respiratory rhythmic head movements ( Moskalenko et al 2001, 2004, 2009, Upledger and Karni 1979, Lockwood and Degenhardts 1998, the reported range of the CRI may include or be the head movements generated by respiratory breathing.…”
Section: Discussionmentioning
confidence: 68%
“…As studies on palpated and measured rates of head movements have shown a wide range (review in Nielson et al 2006), it is possible that different studies may report on different rhythms under the same name, the CRI. Previous reported experimental studies had found a CRI range from 6 -14 cpm ( Moskalenko et al 2001, 2004, 2009, Upledger and Karni 1979, Lockwood and Degenhardts 1998 comparable with the first palpation study (Woods and Woods 1961) reporting a CRI range of 10 -14 cpm. As the mentioned studies above did not report separation of the CRI and the respiratory rhythmic head movements ( Moskalenko et al 2001, 2004, 2009, Upledger and Karni 1979, Lockwood and Degenhardts 1998, the reported range of the CRI may include or be the head movements generated by respiratory breathing.…”
Section: Discussionmentioning
confidence: 68%
“…31 Moskalenko et al (2009) undertook another uncontrolled basic science study of five volunteers investigated with synchronous bioimpedance traces to develop an 'hemoliquorodynamic hypothesis' that allegedly led to unquantified 'changes in lumbar muscle tone and sacral motion'. 32 None of these basic science studies provides evidence supportive of the hypothesis of OCF nor reason for any difference in conclusions from 1999 to 2013.…”
Section: Controversial Practice?mentioning
confidence: 93%
“…Feilding published a book on trepanation ("Blood and Consciousness", 2001) and ran twice (1979 -40 votes, 1983 -139 votes) for British Parliament, with a platform fighting specifically for public funding of trepanation ("Trepanation for the National Health") ( Figure 3A). She now financially supports and co-authors Russian researchers on the relationships between blood and cerebrospinal fluid dynamics and consciousness 20, 21,22 , and supports research on consciousness and psychoactive drugs and the creation of balanced drug policies via the Beckley Foundation (http://beckleyfoundation.org).…”
Section: Amanda Feilding (1943-)mentioning
confidence: 96%
“…The study could not prove physiological changes using MRI methods (not described) but all the individuals are said to be satisfied with the procedure. Halvorson and Feilding coauthored a number of studies on brain blood and cerebrospinal fluid dynamics 20, 21,22,25 . The one most quoted by the ITAG (a translation from an article first published in Russian) concerns people submitted to neurosurgery for different and unstated reasons 20 .…”
Section: Peter Halvorson (1947?-)mentioning
confidence: 99%
See 1 more Smart Citation